Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/nph.14353
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine nucleotide transhydrogenase PntAB is essential for optimal growth and photosynthetic integrity under low‐light mixotrophic conditions in Synechocystis sp. PCC 6803

Abstract: Summary Pyridine nucleotide transhydrogenase (PntAB) is an integral membrane protein complex participating in the regulation of NAD(P)+:NAD(P)H redox homeostasis in various prokaryotic and eukaryotic organisms. In the present study we addressed the function and biological role of PntAB in oxygenic photosynthetic cyanobacteria capable of both autotrophic and heterotrophic growth, with support from structural three‐dimensional (3D)‐modeling. The pntA gene encoding the α subunit of heteromultimeric PntAB in Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…In photosynthetic organisms, the NADH/NAD + status is known to regulate the coordination of nitrogen assimilation and carbon metabolism by various mechanisms (Dutilleul et al, 2005;Kämäräinen et al, 2017;Pétriacq et al, 2017). By applying a number of physiological measurements and the proteomics approach, we showed that the deletion of NdbC has a distinct effect on the metabolism of Synechocystis.…”
Section: Resultsmentioning
confidence: 99%
“…In photosynthetic organisms, the NADH/NAD + status is known to regulate the coordination of nitrogen assimilation and carbon metabolism by various mechanisms (Dutilleul et al, 2005;Kämäräinen et al, 2017;Pétriacq et al, 2017). By applying a number of physiological measurements and the proteomics approach, we showed that the deletion of NdbC has a distinct effect on the metabolism of Synechocystis.…”
Section: Resultsmentioning
confidence: 99%
“…NAD + is converted into NADP + , required as an electron acceptor in linear photosynthetic electron transport, by NAD kinases, of which two are present in Synechocystis (NadK1, NadK2) [109]. The NAD + /NADP + ratio is regulated by pyridine nucleotide transhydrogenase (PntA/PntB), which catalyses electron transfer between the two compounds [110].…”
Section: Nad + and Nadp + Biosynthesismentioning
confidence: 99%
“…PntAu may therefore only be important for the supply of NADP(H) under conditions of limiting light (e.g. during the night) and/or in order to re-oxidize NADH formed by NAD(H)-dependent reactions (Kämäräinen et al 2017). Hence, although PntAu is well-known in fermentative microorganisms it remains unclear what role it may have in cyanobacteria, thereby falling into the category of incompletely known genes.…”
Section: Case Study 2 -Nadp(h)-metabolismmentioning
confidence: 99%